Octopamine signaling in the metazoan pathogen Schistosoma mansoni: localization, small-molecule screening and opportunities for drug development - Nelly El-Sakkary; Steven Chen; Michelle R. Arkin; Conor R. Caffrey; Paula Ribeiro (Disease Models & Mechanisms, 2018)
Schistosomiasis is a tropical disease caused by a flatworm trematode parasite that infects over 200 million people worldwide. Treatment and control of the disease rely on just one drug, praziquantel. The possibility of drug resistance coupled with praziquantel's variable efficacy encourages the identification of new drugs and drug targets. Disruption of neuromuscular homeostasis in parasitic worms is a validated strategy for drug development. In schistosomes, however, much remains to be understood about the organization of the nervous system, its component neurotransmitters and potential for drug discovery. Using synapsin as a neuronal marker, we map the central and peripheral nervous systems in the Schistosoma mansoni adult and schistosomulum (post-infective larva). We discover the widespread presence of octopamine (OA), a tyrosine-derived and invertebrate-specific neurotransmitter involved in neuromuscular coordination. OA labeling facilitated the discovery of two pairs of ganglia in the brain of the adult schistosome, rather than the one pair thus far reported for this and other trematodes. In quantitative phenotypic assays, OA and the structurally related tyrosine-derived phenolamine and catecholamine neurotransmitters differentially modulated schistosomulum motility and length. Similarly, from a screen of 28 drug agonists and antagonists of tyrosine-derivative signaling, certain drugs that act on OA and dopamine receptors induced robust and sometimes complex concentration-dependent effects on schistosome motility and length; in some cases, these effects occurred at concentrations achievable in vivo. The present data advance our knowledge of the organization of the nervous system in this globally important pathogen and identify a number of drugs that interfere with tyrosine-derivative signaling, one or more of which might provide the basis for a new chemotherapeutic approach to treat schistosomiasis. This article has an associated First Person interview with the first author of the paper.